LUDIC SENSES SOCIALIZED BY HANG-GLIDING (Fiep Bulletin - online, 2014)
This work has as its objective to identify the ludicity senses present in the hang-gliding pilots' speeches. We have analyzed the testimonies of an Internet discussion list published in the book Parapente Brasil (2002). Articles and interviews published in the Air magazine, a specialized one in hang-gliding, from no. 01 to 15 were also analyzed. The study is descriptive exploratory, with qualitative approach in which the speeches were examined, under the form of content analysis (Bardin, 2004). We have concluded that hang-gliding promotes an encounter with the ludicity in the pleasure, creation, vertigo, competition and freedom senses. The acquired experience through the regular practice and the ability in handling different types of equipment  together with the resources offered by technology allow the facing of more and more unexpected situations. The speeches reveal that the actors choose the road of ludicity and aesthetics to provide the beauty idea that allows this flight practice. However, the accomplishment of a flight by itself does not guarantee that the activity is ludic. So that the flight becomes a ludic experience, the pilot should let get involved, take possession of the ludic spirit that the moment provides.
Keywords: hang-gliding; ludicity; pleasure.